Doses de nitrogênio para plantas jovens de laranja Valência enxertadas em citrandarins - Zechin, Pedro Henrique Menegazzo (Universidade Federal de São Carlos, 2025)
Orange cultivation holds significant economic importance for Brazil, being intended for both fresh consumption and juice processing. To ensure high productivity and fruit quality, an adequate supply of nutrients is essential. In this context, the objective of this study was to evaluate the effect of different nitrogen (N) doses on young ‘Valencia’ orange plants grafted onto citrandarin rootstocks. The experiment was conducted in a randomized block design, in a split-plot scheme with three replicates. The rootstocks (IAC 3152 Itajobi, IAC 3026 Santa Amélia, and IAC 3073 Barretos) were allocated to the main plots, while the nitrogen doses (0, 60, 120, and 180 g plant⁻¹) were assigned to the subplots. The following variables were evaluated: vegetative development, soil and plant nutrition, gas exchange parameters (photosynthesis and stomatal conductance), HLB severity, and total chlorophyll content. The results showed no significant differences in leaf nitrogen content among the applied doses, indicating nutritional stability during this initial growth phase. However, differences were observed among the rootstocks, with IAC 3152 Itajobi being the most promising in terms of vegetative growth and water use efficiency, while IAC 3026 Santa Amélia showed greater susceptibility to HLB. Nitrogen doses positively influenced chlorophyll content, showing a correlation with increased photosynthetic activity. The findings provide valuable insights for the initial nutritional management of the crop, highlighting the importance of rootstock selection and the rational use of nitrogen fertilization in young plants.
Nitrogen rates for young Valencia orange plants grafted onto citrandarins
Keywords: HLB; Porta-enxerto; Trocas gasosas; Ureia; Rootstock; Gas exchange; Urea; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA